Isolation and Screening of Polyhydroxyalkanoates Producing Bacteria from Pulp, Paper, and Cardboard Industry Wastes - Anish Kumari Bhuwal; Gulab Singh; Neeraj Kumar Aggarwal; Varsha Goyal; Anita Yadav (International Journal of Biomaterials)
Background. Polyhydroxyalkanoates (PHAs) are storage materials that accumulate by various bacteria as energy and carbon reserve materials. They are biodegradable, environmentally friendly, and also biocompatible bioplastics. Unlike petrochemical-based plastics that take several decades to fully degrade, PHAs can be completely degraded within a year by variety of microorganisms into CO2 and water. In the present study, we aim to utilize pulp, paper, and cardboard industry sludge and waste water for the isolation and screening of polyhydroxyalkanoates (PHAs) accumulating bacteria and production of cost-effective PHB using cardboard industry waste water. Results. A total of 42 isolates showed black-blue coloration when stained with Sudan black B, a preliminary screening agent for lipophilic compounds, and a total of 15 isolates showed positive result with Nile blue A staining, a more specific dye for PHA granules. The isolates NAP11 and NAC1 showed maximum PHA production 79.27% and 77.63% with polymer concentration of 5.236 g/L and 4.042 g/L with cardboard industry waste water. Both of the selected isolates, NAP11 and NAC1, were classified up to genus level by studying their morphological and biochemical characteristics and were found to be Enterococcus sp., Brevundimonas sp. and, respectively. Conclusion. The isolates Enterococcus sp. NAP11 and Brevundimonas sp. NAC1 can be considered as good candidates for industrial production of PHB from cardboard industry waste water. We are reporting for the first time the use of cardboard industry waste water as a cultivation medium for the PHB production.